2019
DOI: 10.3390/math7030253
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of “Accurate and Efficient Explicit Approximations of the Colebrook Flow Friction Equation Based on the Wright ω-Function” by DejanBrkić; and Pavel Praks, Mathematics 2019, 7, 34; doi:10.3390/math7010034

Abstract: The Colebrook-White equation is often used for calculation of the friction factor in turbulent regimes; it has succeeded in attracting a great deal of attention from researchers. The Colebrook–White equation is a complex equation where the computation of the friction factor is not direct, and there is a need for trial-error methods or graphical solutions; on the other hand, several researchers have attempted to alter the Colebrook-White equation by explicit formulas with the hope of achieving zero-percent (0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In our recent paper [1] we found that one pair of parentheses is missing in Equation (2). The corrected Equation (2) of the commented article [1] is here given as Equation 1:…”
Section: Typographical Correctionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent paper [1] we found that one pair of parentheses is missing in Equation (2). The corrected Equation (2) of the commented article [1] is here given as Equation 1:…”
Section: Typographical Correctionsmentioning
confidence: 99%
“…The nature of these errors is typographical and does not affect other formulas or findings. We apologize to the readers for any inconvenience caused by these two typographical errors, and we want to thank the authors of the discussion [2] for pointing out the errors in the second here corrected equation.…”
Section: Typographical Correctionsmentioning
confidence: 99%
See 3 more Smart Citations